Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Upaya Pemajuan Hak Asasi Manusia (HAM) di Era Digital - Li, Dwiki (Pancasila and Civics Education Journal, 2025)
ABSTRACTThe increasing violations of human rights in the digital era have prompted governments to implement various preventive measures to ensure the protection of these rights, one of which is the promotion of human rights through civic education. A crucial component in this promotion is the role of teachers. This article aims to explore the role and challenges faced by civic education teachers in advancing human rights in the digital era. The study employs a literature review methodology. The findings indicate that teachers play a strategic role as facilitators of understanding digital human rights, internalising the values of Pancasila, serving as ethical behaviour role models, developing digital literacy, and being adaptive active learners in response to technological advancements. However, challenges include limited understanding of human rights content, an emphasis on obligations rather than rights, and issues related to digital crimes. The research recommends a transformation in teaching approaches from textual-normative to contextual-applicative, enhancing teachers' capacities through training, and fostering synergy between schools, families, and communities to create an educational ecosystem that supports the emergence of responsible and human rights-conscious digital citizens. Keywords: PPKn Teachers Role; Promotion of Human Rights; Digital Era ABSTRAKPelanggaran Hak Asasi Manusia di Era Digital semakin meningkat membuat pemerintah mengeluarkan berbagai upaya preventif dalam menjamin perlindungan Hak Asasi Manusia salah satunya dengan upaya pemajuan Hak Asasi Manusia melalui Pendidikan Kewarganegaraan. Salah satu komponen penting dalam pemajuan Hak Asasi Manusia melalui Pendidikan Kewarganegaraan adalah guru.  Artikel ini bertujuan untuk mengetahui peran dan tantangan guru PKn dalam Upaya Pemajuan Hak Asasi Manusia di Era Digital. Artikel ini menggunakan Metode penelitian yang digunakan merupakan penelitian studi pustaka. Hasil penelitian menunjukkan bahwa guru memiliki peran strategis sebagai fasilitator pemahaman HAM digital, penginternalisasi nilai-nilai Pancasila, panutan perilaku etis, pengembang literasi digital, dan pembelajar aktif yang adaptif terhadap perkembangan teknologi. Namun, tantangan yang dihadapi meliputi keterbatasan pemahaman materi HAM, penekanan pada kewajiban daripada hak, dan isu kejahatan digital. Penelitian ini merekomendasikan perlunya transformasi pendekatan pembelajaran dari tekstual-normatif menjadi kontekstual-aplikatif, peningkatan kapasitas guru melalui pelatihan, serta sinergi antara sekolah, keluarga, dan masyarakat untuk menciptakan ekosistem pendidikan yang mendukung terwujudnya warga negara digital yang bertanggung jawab dan berkesadaran HAM.Kata Kunci: Peran Guru PPKn; Pemajuan Hak Asasi Manusia; Era Digital